The Influence of Knowledge, Lifestyle, and Religiosity of Jambi University FEB Students on Decisions to Use Fintech (Online Loans) from an Islamic Economics Perspective - Nuraini, Indah; Fitri, Lucky Enggrani; Lubis, Paulina (Money: Journal of Financial and Islamic Banking, 2024)
Purpose – This research aims to determine the influence of knowledge, lifestyle, and religiosity of economics and business faculty students on the decision to use fintech (online loans) from an Islamic economics perspective. Method – The approach used in this research is a quantitative method using data analysis methods in the form of validity tests, reliability tests, and multiple linear regression. Results – The research results show that knowledge and lifestyle variables have a positive and significant effect on the decision to use online loans. From the results of the calculated t-hypothesis test on variable X1 which is 5.794 and X2 which is 4.255 with a significance level of 0.000. Because the calculated t is greater than the t table, namely (5.794 > 0.677) and the significant value is 0.00 < 0.05. Meanwhile, the religiosity variable (X3) has no significant effect on the decision to use online loans with a significant value of 0.699 > 0.05 Originality – This research reveals the influence of knowledge, lifestyle, and religiosity of Jambi University FEB students on the decision to use fintech (online loans) from an Islamic economic perspective Implications – Student knowledge, lifestyle, and religiosity can help students make decisions about using online loans.